PERFORMANCE IMPROVEMENT STRATEGIES IN FINANCIAL, LEARNING AND GROWTH PERSPECTIVES THROUGH IMPLEMENTING THE INTEGRATION OF LEAN WITH SIX SIGMA (DMAIC) CONCEPTS IN THE PACKAGING DRINKING WATER INDUSTRY IN MAKASSAR CITY - ahmad, Lamatinulu (Center for Study and Journal Management FTI UMI, 2021)
The growth of bottled drinking water is currently growing in line with the increasing needs of the community, however, in its operational activities, several problems are still found. The problems are related to the problem of activities that are not useful (waste) in the aspects of finance, learning, and growth. Based on these problems, in this study, an analysis was carried out by applying the integration of the concept of Lean and Six Sigma. The research method approach is carried out by identifying the types of activities that are not useful (waste) and analyzed by the stages Define, Measure), Improve, and Control with the abbreviation DMAIC analysis. The method of data collection was carried out by direct survey, interview, and questionnaire instrument distribution. The results of this study identify activities that are not useful (waste) in the form of findings of the amount of non-productive work time, low work motivation, low frequency of employee education and training activities, loss of sales turnover due to consumer movement to buy other brands of products, it is still found that the lowest sales volume occurs. Based on the stages of DMAIC analysis, 10 root causes and strategies of waste are found from a financial perspective, and 8 on the aspects of growth and learning.